Decoding resistant hypertension signalling pathways - Parreira, Ricardo Cambraia; Guimarães Lacerda, Leandro Heleno; Vasconcellos, Rebecca; Lima, Swiany Silveira; Santos, Anderson Kenedy; Fontana, Vanessa; Sandrim, Valéria Cristina [UNESP]; Resende, Rodrigo Ribeiro (Portland Press, 2017)
Resistant hypertension (RH) is a clinical condition in which the hypertensive patient has become resistant to drug therapy and is often associated with increased cardiovascular morbidity and mortality. Several signalling pathways have been studied and related to the development and progression of RH: modulation of sympathetic activity by leptin and aldosterone, primary aldosteronism, arterial stiffness, endothelial dysfunction and variations in the renin-angiotensin-aldosterone system (RAAS). miRNAs comprise a family of small non-coding RNAs that participate in the regulation of gene expression at post-transcriptional level. miRNAs are involved in the development of both cardiovascular damage and hypertension. Little is known of the molecular mechanisms that lead to development and progression of this condition. This review aims to cover the potential roles of miRNAs in the mechanisms associated with the development and consequences of RH, and explore the current state of the art of diagnostic and therapeutic tools based on miRNA approaches.